Career Management Strategy for Position Succession in PT SMPD Production Unit - Muhammad Thariq; Dedy Sushandoyo (Green Publisher Indonesia, 2025)
In the competitive cement industry landscape, PT SMPD faces significant challenges in ensuring competent successors for key positions. This research proposes a comprehensive career management strategy to address this issue, focusing on leadership development and succession planning, competency management, cultural transformation, and strategic alignment. Using a qualitative methodology, data was collected through interviews, observations, and document analyses over three months at PT SMPD. The findings indicated considerable gaps in recruitment, competency development, and leadership training. The proposed strategy includes a 24-month phased implementation plan starting with succession planning and leadership development, followed by competency assessment, performance management, and HR technology integration. The strategy emphasised strong executive support, dedicated cross-functional teams, effective communication, and prioritising data and analysis. The results show that a structured approach to career management can significantly improve leadership pathways, employee engagement, and organisational performance. By implementing this strategy, PT SMPD can develop a future-ready workforce, achieve strategic goals, and emerge as an industry leader in career management practices.